INTERGENERATION SKILLS TRANSFERENCE, UNCERTAINTY AND EMANCIPATION IN WORKERS' FORMATION - Moacir Fernando Viegas (Editora da Universidade de Santa Cruz do Sul, 2011)
The present article was originated in an academic research aimed to describe and analyze, through the life story of sixteen workers who went to Sine Agency (a job agency) of Santa Cruz do Sul, the ways in which workers of old and new generations experience and represent the changes in work and their cultural background, especially their education and their children. We highlight three issues that emerged from the analysis and that help us understand the phenomenon in question: a) the intergenerational transfer of skills as a significant part of the trajectory of training, b) the uncertainty that characterizes the lives of the interviewed people, which reflects the difficulty of establishing parameters of their formation, c) the emancipatory possibilities contained in the paths of formation of these subjects in the context of the information economy. For this research, we made use of deep semi-structured interviews. Keywords: education and work. Education of youth and adults. Emancipation. Critical theory. Life stories.